Exploratory Data Analysis terhadap Kepadatan Penumpang Kereta Rel Listrik - Feliks Victor Parningotan Samosir; Loudry Palmarums Mustamu; Erik Dwi Anggara; Albertus Indarko Wiyogo; Andreas Widjaja (Maranatha University Press, 2021)
The existence of the Kereta Rel Listrik Commuter Line as the backbone of transportation in the Jakarta - Bogor - Depok - Tangerang - Bekasi - Banten area has a very important role for commuter mobility around Daerah Khusus Ibukota Jakarta. With an average number of 1.1 million passengers per day, Kereta Rel Listrik is one of the factors supporting Indonesia's economy and growth in various sectors. On the other hand, the Covid-19 pandemic that hit the world caused restrictions on human movement which resulted in a decline in all economic sectors. The purpose of this research is to obtain optimal train schedule recommendations for the operation of the Kereta Rel Listrik Commuter Line in the Rangkasbitung - Tanah Abang service to carry passengers optimally while adhering to the physical distancing protocol set by the Minister of Transportation to prevent the wider spread of Covid-19. With such a large amount of data that must be processed, Exploratory Data Analysis is one of the choices we take to process the above data to get satisfactory results.